Assessment of the Reality of Higher Education in Iraq from the Perspective of Iraqi University Students - Saud, Prof. Dr. Abdul-Razzaq Mohsen Saud (Sulaimani Journal for Humanities, 2026)
The study aimed to identify: (1) The assessment of the reality of higher education in Iraq from the perspective of university students, (2) The assessment of the reality of higher education in Iraq from the perspective of university students according to the variables of gender (male – female), specialization (scientific – humanities), and academic year (first – fourth). To achieve the study objectives, a questionnaire titled "Assessment of the Reality of Higher Education in Iraq from the Perspective of Iraqi University Students" was developed. Its face validity and reliability were established. The total number of respondents was 633 students, selected from 13 universities, including 237 students from scientific specializations and 396 from humanities specializations. The sample consisted of 159 male students and 474 female students, distributed as follows: 192 first-year students, 204 second-year students, 96 third-year students, and 141 fourth-year students. For statistical data analysis, Fisher’s equation and the Chi-square equation were used. The results indicated that university students' overall assessment of higher education in Iraq was positive. The findings also revealed statistically significant differences in 16 questionnaire items based on gender, favoring males over females, while the remaining 16 items showed no gender-based differences. Regarding specialization, significant differences were observed in only seven items, favoring scientific specializations over humanities, while no differences appeared in the remaining 25 items. Concerning academic year, significant differences were found in five items, favoring fourth-year students over first-year students, while no differences appeared in the remaining 27 items.
Keywords: Assessment; Higher Education; University Students